Aplicação do descritor de paisagem HAND para obtenção de manchas de inundação utilizando modelos digitais de elevação em diferentes compartimentos geomorfológicos - Araujo, Gustavo Schefelbanis (2023)
Due to climate change and human actions, flood events will become more and more frequent. Flooding is the natural phenomena that most affects the planet, remaining present across the globe. In order to mitigate the problems caused by this kind of event, this work proposes a decision-making support tool for flood events and was developed in the municipalities of Blumenau and Itajaí due to the availability of data. This tool was produced based on the application of the landscape descriptor Heith Above Nearest Drainage model (HAND), with a different digital elevation models (DEM) — SRTM, ASTER e Alos Palsar —, with analysis of different drainage thresholds, in order to obtain flood patches and their corresponding precipitation events. The two municipalities have different topographical characteristics, with Itajaí in the plain, while Blumenau in more rugged terrain. For the municipality of Itajaí, due to the complexity of the local drainage network and topographic characteristics, it was not possible to generate the flow grid by the HAND from the DEM and available resolutions, which, thus, presented a limiting factor in the application of the HAND, preventing the obtaining of flood spots for the region. In the municipality of Blumenau, it was possible to carry out the complete application of the methodology, obtaining the proposed tool. The calibration of the threshold drenage proved to be one of the main factors for obtaining a good result in the modeling. As for the analysis of different MDEs, SRTM and Alos Palsar obtained similar results, with superior performance than ASTER. Also, as the simulated quota increased, the results became more accurate regardless of the DEM used. Therefore, DEM Alos Palsar was chosen to adjust the flood spots, resulting from the application of the HAND, to precipitation events. For this analysis, the events were separated into two phases, pre- and post-1992, since this year an intervention was carried out to contain flood events in the watershed of the Itajaí-Açu river, with the construction of a dam. The pre-1992 adjustment obtained an (R²) of 0.80, while the post-1992 adjustment obtained an (R²) 0.59, and the pre-1992 behavior is also represented when the basin is in the saturated condition. This result indicates that the proposed tool is capable of representing flood events, and can become an ally in decision-making processes in the face of possible flood events.